The Cloud Computing Opportunities and Challenges in Electronic Document Management - Aviazka Firdhaussi Azmir; Luki Wijayanti (Record and Library Journal, 2022)
Background of the study: Technological developments have encouraged the creation of cloud computing technology that allows access to information from everywhere via the internet. The use of cloud computing in managing electronic documents can manage document storage without having storage specialists, reducing the need for physical storage space, and access flexibility. But behind the benefits offered, some risks must be anticipated by the organization. Purpose: This study aims to determine the opportunities and challenges of using cloud computing in electronic document management. Method: This study uses the Systematic Literature Review method on the literature available in the Google Scholar database from 2017 to 2022. Findings: Based on the results of an analysis conducted on 20 selected articles, it was found that the opportunity of cloud computing in electronic document management is to increase efficiency in managing electronic documents, especially in terms of centralized document storage, increasing productivity, and response time of business processes, and cost efficiency. Meanwhile, the challenges are related to data security, system stability, authentication, and disaster preparedness, both from nature and cybercrime. Conclusion: The research recommends that organizations using cloud computing to manage their electronic document must provide compatible and good security systems.